2021
DOI: 10.1002/cam4.4183
|View full text |Cite
|
Sign up to set email alerts
|

Trends in cancer imaging by indication, care setting, and hospital type during the COVID‐19 pandemic and recovery at four hospitals in Massachusetts

Abstract: Background We aimed to investigate the effects of COVID‐19 on computed tomography (CT) imaging of cancer. Methods Cancer‐related CTs performed at one academic hospital and three affiliated community hospitals in Massachusetts were retrospectively analyzed. Three periods of 2020 were considered as follows: pre‐COVID‐19 (1/5/20–3/14/20), COVID‐19 peak (3/15/20–5/2/20), and post‐COVID‐19 peak (5/3/20–11/14/20). 15 March 2020 was the day a state of emergency was declared in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…40 Nonurgent imaging services that were considered general elective screening appointments, particularly lung and breast screenings, were also impacted, 41 with cancer surveillance and diagnostic services dropping by more than 50%. 39 The observed changes in surgery and imaging utilization between our rural and urban patients likely reflect the impact of facility closures, reduced lung and breast imaging capacity at facilities, travel barriers, combined with patients’ willingness to go to medical clinics as well as access to medical care (eg, loss of health insurance). For instance, rural patients in our study were significantly older than urban patients, which may have led to rural patients avoiding hospitals for fear of contracting COVID‐19 as elderly individuals are more susceptible to having severe disease.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…40 Nonurgent imaging services that were considered general elective screening appointments, particularly lung and breast screenings, were also impacted, 41 with cancer surveillance and diagnostic services dropping by more than 50%. 39 The observed changes in surgery and imaging utilization between our rural and urban patients likely reflect the impact of facility closures, reduced lung and breast imaging capacity at facilities, travel barriers, combined with patients’ willingness to go to medical clinics as well as access to medical care (eg, loss of health insurance). For instance, rural patients in our study were significantly older than urban patients, which may have led to rural patients avoiding hospitals for fear of contracting COVID‐19 as elderly individuals are more susceptible to having severe disease.…”
Section: Discussionmentioning
confidence: 95%
“…We observed that rural versus urban patients were more likely to be older, not employed, uninsured, and have unhealthy behaviors (eg, smoking), consistent with prior research. 35 36 and imaging services [37][38][39] were delayed or cancelled during the initial phase of the COVID-9 pandemic. Nearly all states, including Utah, issued emergency executive orders postponing elective surgeries and medical procedures between March and April 2020.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies conducted in Canada, the United States, Brazil, France, Qatar, Taiwan, and Belgium, COVID-19 had a dramatic impact on mammography and/or MRI of the breast (À10 to À100%) [11, 14,15,16 ,34-37,40,43,44,46]. A significant drop in cancer screening computed tomography imaging in the United States (À49 to À81.7%) [32,37] ], and oral cancer in Taiwan (À50%) [43]. Cancer screening rates were impacted according to the prevalence of COVID-19 in the respective countries, poorly controlled COVID-19 infection rates, or the preparedness of the healthcare systems in dealing with crises such as the pandemic.…”
Section: Covid-19 and Cancer Screening Programmentioning
confidence: 99%
“…In studies conducted in Canada, the United States, Brazil, France, Qatar, Taiwan, and Belgium, COVID-19 had a dramatic impact on mammography and/or MRI of the breast (−10 to −100%) [ 11 , 14 , 15 , 16 ▪ , 19 ▪ , 21 ▪ , 22 ▪ , 25 , 28 , 30 ▪▪ , 34 37 , 40 , 43 , 44 , 46 ]. A significant drop in cancer screening computed tomography imaging in the United States (−49 to −81.7%) [ 32 , 37 ] and diagnostic radiology rates (−16%) was observed in Switzerland [ 17 ]. Reductions in cancer screening were reported for cervical cancer (−7.5 to −90%) in Canada, the United States, Brazil, France, Taiwan, Belgium, and 17 selected low- and middle-income countries (LMICs) [ 19 ▪ , 21 ▪ 23 ▪ , 30 ▪▪ , 33 , 35 ▪ , 36 , 38 – 40 , 43 , 46 ].…”
Section: Covid-19 and Cancer Screening Programmentioning
confidence: 99%